2010
DOI: 10.1242/jeb.037168
|View full text |Cite
|
Sign up to set email alerts
|

Condition and mass impact oxygen stores and dive duration in adult female northern elephant seals

Abstract: SUMMARYThe range of foraging behaviors available to deep-diving, air-breathing marine vertebrates is constrained by their physiological capacity to breath-hold dive. We measured body oxygen stores (blood volume and muscle myoglobin) and diving behavior in adult female northern elephant seals, Mirounga angustirostris, to investigate age-related effects on diving performance. Blood volume averaged 74.4±17.0liters in female elephant seals or 20.2±2.0% of body mass. Plasma volume averaged 32.2±7.8liters or 8.7±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 61 publications
4
75
1
1
Order By: Relevance
“…In the Indian Ocean sector, this zone broadens latitudinally in the Kerguelen region (Orsi et al 1995) and this sector seems to represent a large region of un favourable foraging conditions for SES. Despite our results supporting previous findings that dive capacity increases throughout the duration of the foraging trips (Bennett et al 2001, Hassrick et al 2010, Mc Intyre et al 2011b), both T 200 and diving depth were also found to influence dive duration in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…In the Indian Ocean sector, this zone broadens latitudinally in the Kerguelen region (Orsi et al 1995) and this sector seems to represent a large region of un favourable foraging conditions for SES. Despite our results supporting previous findings that dive capacity increases throughout the duration of the foraging trips (Bennett et al 2001, Hassrick et al 2010, Mc Intyre et al 2011b), both T 200 and diving depth were also found to influence dive duration in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…Muscle O 2 stores, as indicated by Mb concentrations, were higher than previously reported in Weddell seals (Ponganis et al 1993;Kanatous et al 2002;Hindle et al 2011), but were also maintained across the winter. As muscle Mb loads often correlate with dive durations (Noren and Williams 2000;Lestyk et al 2009), higher Mb concentrations in deep-diving Weddell seals make their O 2 -storage capacities more similar to those previously reported in other phocid species capable of extended breath hold diving Lestyk et al 2009;Hassrick et al 2010). That Weddell seals expend energy to continue producing equivalent RBCs and iron-containing O 2 -carrying proteins during all times of the year (i.e., reduced and intense foraging periods, and the energetically expensive molt period), and also through senescence (Hindle et al 2009 demonstrates the importance of maintaining aerobic diving capacities.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast to otariids, the Phocidae family appears to follow a different pattern. In addition to TBO 2 and muscle biochemistry being conserved in Weddell seals, the northern elephant seal (Mirounga angustirostris) did not exhibit any changes in factors contributing to TBO 2 or the cADL across the post-molt or post-breeding foraging trips (Hassrick et al 2010), and studies show that harbor seal (Phoca vitulina) muscle biochemistry does not change seasonally (Burns unpublished). Weddell seals and other phocids forage on unreliable prey resources spanning great distances in order to accumulate some or all of the reserves necessary for energetically costly periods of reproduction and the annual molt (Costa and Shaffer 2012).…”
mentioning
confidence: 99%
“…For example, seals may prolong bottom duration to increase foraging effort in richer feeding grounds, an idea supported by theoretical and empirical studies on the diving behaviour of some seal species [7,49]. Second, changes in body size may affect bottom duration, because large body mass increases oxygen-carrying capacity while simultaneously reducing the rate of oxygen use, allowing seals to stay underwater longer [50,51]. Third, seasonal hypometabolism (i.e.…”
Section: Discussion (A) Buoyancy Determines Locomotor Costs Of Swimmingmentioning
confidence: 99%